Optimal Allocations in the Construction of k-Out-of-n Reliability Systems - Derman, C.; Lieberman, G. J.; Ross, S. M. (Management Science, 1974)
We want to build n components so as to form an n component system which will function if at least k of the components function. If x dollars are invested in building a component, then this component will function with probability P(x). Given a total income of A dollars, the problem of interest is to determine how much money we should invest in each component so as to maximize the probability of attaining a functioning system. This problem is considered both in the sequential and in the nonsequential cases. Conditions under which it is optimal to allocate A/n units at each stage, when A is your initial fortune, are presented. The special case P(x) = min(x, 1) is also considered in detail.